Analisis Produktivitas Alat Berat pada Pekerjaan Peremajaan Sawit pada Lahan Gambut - Muhammad Maulidin Z; Fakhrul Rozi Yamali; Riki Saputra; Fakhrul Rozi Yamali (Universitas Batanghari, 2023)
In construction work, whether it's building a building, road, bridge or other construction work, you really need tools that can support the work. The tools used in construction work are not only light tools that can already be used in building simple constructions but for construction that is not designed to be simple, heavy equipment is needed. Tools can be a reliable solution to assist the process of building facilities and infrastructure. This study aims to determine the productivity and the amount of heavy equipment needed as well as to determine the productivity of costs and time and human resources used. The research was conducted on the palm oil rejuvenation project for the people of Sumber Agung village, Sungai Gelam sub-district, Jambi province. The data used consists of primary data, namely interview data and secondary data, which consists of contract documents, and heavy equipment unit price reports. The data obtained were analyzed or compared with direct observations. From the results of the analysis, it was found that the number of heavy equipment needed in the palm oil rejuvenation work of the people of Sumber Agung village was 12 excavators and 10 chainsaw tools. With a work duration of 85 days or 598 working hours, the costs required for excavation and felling of oil palm trees for oil palm rejuvenation of the people of Sumber Agung village are Rp. 2,776,267,420. While in planning the amount of costs required for the work is Rp. 3,911,374,900.